(untitled) (Kriminalističke teme, 2019)
Inspiracija za rad i problem (i) koji se radom oslovljava (ju): Razvojem informaciono-komunikacionih tehnologija stvara se sve više mogućnosti sajber-kriminalcima da na lagan način “upadnu” u sistem pojedinca ili kompanija i da načine štetu. U radu će biti opisan razvoj sajber kriminala, oblici zloupotreba i prijevara, te tehnike koje se koriste za otkrivanje počinilaca. Izvlačenje ovih podataka, njihovo tumačenje i prognoziranje, te jednostavno prezentiranje pred sudom, predstavljaju moćan alat u istražnim postupcima. Dakle, nove tehnologije, novi pristup izvršenja krivičnih djela, i otkrivanja istih, inspiracija je za sve istraživače krivičnopravnih i kriminalističkih nauka. Ciljevi rada (naučni i/ili društveni): Na osnovu uočenog problema istraživanja definisan je i predmet istraživanja: predmet rada ima za cilj da objasni metode primjene digitalne forenzike u otkrivanju počinilaca sajber kriminala. Metodologija/Dizajn: Iako se digitalni dokazi, do prije nekoliko godina u našem okruženju, nisu niti priznavali u sudskim procesima, danas je situacija sasvim druga, jer ovi dokazi ukoliko se prikupe, i obrade na adekvatan način, te prezentiraju uz pomoć propisanih procedura koji se forenzičari moraju pridržavati, tada su dokazi ravnopravni sa ostalim materijalnim dokazima. U konstelaciji sa navedenim, postavljen je sljedeći problem, a ujedno i hipoteza istraživanja: Da li je moguće metodama digitalne forenzike obezbijediti relevantne dokaze o počiniocima i krivičnim djelima za sudske postupke validne dokaze sajber kriminala? Ograničenja istraživanja/rada: Jedan od bitnih faktora ograničenja istraživanja sajber kriminala, predstavlja ubrzani tehnološki razvoj, te samim tim i metode izvršenja izvršilaca, koje su svakim danom sve savremenije, a tehnološka pismenost u Bosni i Hercegovini, ne prati taj korak. Razvojem informacioni tehnologija, zahtijeva prije svega obra-zovni sistem prilagođem novim dostignućima, tehnološku pismenost istražitelja itd. Rezultati/Nalazi: Istina je da koliko god uložili u sigurnost, to ne znači da će informacijski sistem biti u potpunosti siguran te da smo oslobođeni problema. U Bosni i Hercegovini do sada nije provedeno relevantno i sveobuhvatno istraživanje o pojavnosti i rasprostranjenosti ovog kriminala. Zato se mora reći da je u sigurnosnom smislu Bosna i Hercegovina nedovoljno istraženo područje. Bosna i Hercegovina nema ni strategiju ni institucije za rješavanje pitanja sajber kriminala i sajber sigurnosnih prijetnji. Ukoliko se obezbijede ulaganja u razvoj ove discipline kako u materijalne tako i u ljudske resurse, trebalo bi da se smanje ozbiljni problemi prijetnji od hakiranja internet stranica do drugih oblika ovog kriminala. Generalni zaključak: Digitalna forenzika će nastaviti da se razvija i postat će sigurno moćna tehnika za otkrivanje digitalnih dokaza. Da bi taj razvoj bio nesmetan potrebno je da ga prati zadovoljavajuća pravna regulativa i da država ne predstavlja usporavajući faktor. Opravdanost istraživanja/rada:Tendencije učestalosti izvršenja krivičnih djela iz obla-sti sajber kriminala, uzima sve veći primat kako u svijetu, tako i u Bosni i Hercegovini. Zakonska legislativa je prva stepenica u sistematskom pristupu ovom problemu, koji treba u kontinuitetu dorađivati, mijenjati, uporedo sa razvojem tehnološki dostignuća i razvojem istih, kako bi bili na punom tragu izvršiocima ovih krivičnih djela. The Methods of Detection Cyber Crime Into Digital Forensics Reason (s) for writing and research problem (s): By developing information-communication techniques, more and more cyber-criminals are being created to easily "infiltrate" the system of an individual or a company and make damage. The paper will describe the development of cybercrime, forms of abuse and fraud, and technologies used to detect perpetrators. Drawing these data, their interpretation, and forecasting, and simply presenting in court, are a powerful tool in investigative proceedings. Thus, new technologies, a new approach to the perpetration of criminal offenses, and their discovery, is an inspiration for all investigators of criminal law and criminology. Goals of this paper (scientific and/or social): Based on the identified research problem definition and subject matter of research: the subject of the paper aims to explain the methods of applying digital forensics to detecting cybercriminals. Methodology/Design: Although digital evidence, even a few years ago in our environment, did not admit it to judicial proceedings, today’s situation is quite different, as this evidence is collected and processed in an adequate manner and presented with the help of prescribed procedures that must be respected by forensicates , then the evidence is equated with other material evidence. In the constellation of the above mentioned, the next problem has been raised, and the hypothesis of the research is: Is it possible to provide relevant forensic evidence of perpetrators and criminal offenses of cybercrime to judicial proceedings? Research/paper limitations: One of the key factors of cyber-crime limitation is the accelerated technological development, and thus the execution methods of perpetrators, which are more and more contemporary and technological literacy in Bosnia and Herzegovina, are not following this step. With the development of information technology, I primarily adapt the education system to new achievements, the technological literacy of investigators and so on. Results/Findings: It is true that as far as security is concerned, this does not mean that the information system will be completely safe and free from the problem. So far, no relevant and comprehensive investigation into the occurrence and spread of this crime has been carried out in Bosnia and Herzegovina. That is why it has to be said that, in the security sense, Bosnia and Herzegovina is insufficiently explored. Bosnia and Herzegovina have no strategy or institution to address cybercrime issues and cyber security threats. If investment in the development of this discipline is provided both in material and human resources, serious threats from hacking websites to other forms of this crime should be reduced. General conclusion: Digital forensics will continue to develop and will become a powerful technique for detecting digital evidence. In order for this development to be undisturbed it is necessary to follow a satisfactory legal regulation and not to represent a decelerating factor. Research/paper validity: The tendency of the frequency of cybercriminal crime is growing in the world, as well as in Bosnia and Herzegovina. Legislative legislation is the first step in the systematic approach to this issue, which needs to be continually updated, altered, alongside the development of technological achievements and development, to be in full swing for the perpetrators of these criminal offenses.